Opportunities for eco-efficiency at Summerpride Foods Ltd.: a pineapple processing factory - Venters, Bruce Russell Ainsley (Rhodes University, Faculty of Commerce, Investec Business School, 2007)
International awareness and demands for the protection of the environment by the public on industry has only been pushed into the limelight in the past couple of decades. Prior to this it could be argued that it was accepted that environmental protection and economic development were at odds. However it has since been recognised that there is a need to achieve environmental sustainability, the concept of which was released in the 1987 Brundtland Report released by the United Nations. There are a number of ways that industry can reduce its impact on the environment and thus help reach this goal. While some advocated that stricter legislation would result in greater innovation by industry in "cleaning-up" its act, such as the Porter Hypothesis, there were also a number of new concepts and voluntary industry codes being developed. These new practices and codes have been promoted by organisations such as the International Chamber of Commerce and include technological improvements within organisations and improved resource productivity. The aim of this case study research was to find out what the environmental policy and related performance of Summerpride Foods Ltd, a pineapple processing factory in East London was and does an understanding of its environmental performance provide insights for improved efficiency. This involved the identification and analysis of what resources were used during the processing of pineapples as well as making recommendations that would result in increased efficiencies of their use. Due to the number of resources identified, only the use of water and coal which were ranked as having the highest impact were investigated further. The literature review showed that there are industry moves to applying cleaner production and eco-efficiency concepts as a means to attaining environmental sustainability. There are a number of voluntary environmental management system standards and codes that organisations can subscribe to with most probably the ISO 14001 standard being the most internationally recognised. There are many benefits to organisations adopting such standards. The use of lifecycle assessments is a useful tool that can be used to assess the environmental impact of a product through its entire life and thus enable one to identify all resources used and their impact, as well as to provide the information required to quantify areas where the greatest improvements can be made. The results of this research showed that at the start of the study, there was no formal environmental policy in place at Summerpride Foods Ltd and that this was starting to become a requirement with some customers. The detailed results which focused on water and coal usage showed that current operating methods do not recognise the importance of any wastage and that there are a number of changes that could be made that would not only result in better efficiency of use but would also result in substantial financial savings to the organisation. Summerpride Foods Ltd currently has a number of systems in place that help reduce its impact on the environment but these are not formally recorded. Summerpride Foods Ltd should adopt the principles of eco-efficiency and record all systems that impact on the environment. This would be the first step to attaining a formal environmental management system accreditation which due the increasing competitiveness of the international market in which Summerpride Foods Ltd operates, would give it a degree of advantage over those competing pineapples processing factories that do not have such accreditation.
Keywords: Summerpride Foods Ltd. (South Africa); Environmental protection -- South Africa; Industries -- Environmental aspects -- South Africa; Pineapple industry -- South Africa; Environmental policy -- South Africa; Sustainable development -- South Africa